Mental health correlates of substance use behaviors among a nationally representative sample of juvenile offenders. Issue 1 (15th December 2021) - Proctor, Steven L.; Kopak, Albert M.
Abstract : Purpose: This paper aims to extend previous findings by identifying the mental health correlates of both acute and chronic substance use behaviors among a large nationally representative sample of juvenile offenders. Design/methodology/approach: Survey of Youth in Residential Placement interview data from 6, 920 juvenile offenders (76% male) detained in 290 US facilities were analyzed to determine bivariate relationships between two indicators of substance use (acute and chronic) and seven mental health domains (depression/isolation, anxiety, anger, trauma, inattention, hallucinations and suicidality). Findings: Prevalence rates of above average indications for all seven mental health domains were significantly higher among offenders under the influence of a substance at the time they committed their instant offense compared to those not under the influence. Offenders with above average indications in the seven studied mental health areas reported a higher level of chronic effects of substance use relative to those with average or below mental health indications. Practical implications: The results have important implications for the assessment and treatment of co-occurring mental health issues among juvenile offenders with substance use issues. Juveniles with above average mental health indications may be more prone to experiencing a number of substance-related problems. Observed results may guide the implementation of routine assessment procedures at the juvenile detention level. Intake specialists should screen and administer comprehensive mental health assessments for juveniles who report substance intoxication at the time of their instant offense. Juvenile offenders who report clinical levels of mental health symptoms should receive a comprehensive assessment of substance use and related problems. Originality/value: Although the co-occurrence of substance use and mental health issues among juvenile justice involved populations is well documented, previous research studies in this area have included a number of limitations. Relatively small offender sample populations, often from a single facility, warrant further work with a large, nationally representative sample of juvenile offenders. Inconsistency in measures of substance use and the failure to distinguish between acute and chronic measures of substance use in prior studies also require further investigation. This study contributes to the extant co-occurring substance use and mental health knowledge base by identifying the mental health correlates of both acute and chronic substance use behaviors among a large nationally representative sample of juvenile offenders.